Developing variant-adapted COVID-19 vaccines to improve protection against Omicron and other recent variants: a plain language summary - Shanti Pather; Alexander Muik; Ruben Rizzi; Federico Mensa (Taylor & Francis Group, 2024)
SummaryWhat are variant-adapted COVID-19 vaccines?The COVID-19 vaccine developed by BioNTech and Pfizer is known as BNT162b2 (Comirnaty). BNT162b2 contains messenger RNA, or mRNA, from SARS-CoV-2. SARS-CoV-2 is the virus responsible for COVID-19. mRNA is a type of genetic material that contains the instructions that tell cells in the body how to make a protein. The mRNA in BNT162b2 tells the body to make one of the proteins from SARS-CoV-2 known as the spike protein.This teaches the body's defense system, known as the immune system, to recognize and respond to a SARS-CoV-2 infection.The BNT162b2 vaccine contains mRNA from the first SARS-CoV-2 virus, which was detected in December 2019. Since this original vaccine was developed, the SARS-CoV-2 virus has evolved, resulting in the appearance of new versions of the virus, known as variants. Certain variants that might be more concerning for public health are labeled as either 'variants of concern' or 'variants of interest' by the World Health Organization (WHO). Variants have differences in their proteins compared with the original virus that can affect how well the original vaccine works against them. Therefore, BioNTech and Pfizer developed updated versions of the BNT162b2 vaccine that contain mRNA from certain variants. These new vaccines are called variant-adapted COVID-19 mRNA vaccines.Another company, Moderna, has also developed their own variant-adapted versions of their COVID-19 mRNA vaccine, mRNA-1273 (SpikeVax).Variant-adapted vaccines can contain parts of the variant mRNA either in addition to, or instead of, that from the original virus. Vaccines that contain mRNA from two different viruses are known as bivalent, whereas vaccines that contain mRNA from a single virus are called monovalent.